ElectroM: ElectroMechanical dynamic code[Formula presented] - Cunha, Americo (2023)
Electromechanical systems are integral to modern technologies and their accurate simulation is vital for understanding system behavior and optimizing designs. ElectroM, a MATLAB-based open-source software tool, provides advanced capabilities for simulating and analyzing such systems, offering two types of coupling formulations between mechanical and electrical domains, and a module for obtaining dimensionless groups, enabling dimensional analysis and a deeper physical understanding of the problem. This multifaceted approach ensures ElectroM's value not only in research but also as an educational tool, assisting in the intuitive understanding and teaching of complex electromechanical dynamics.